DEMDATA: The Austrian-Czech institutional long term care project – design and protocol of a two-centre cross sectional study - Auer, Stefanie (BMC Health Serv Res, 2017)
BACKGROUND: The organization of long-term care is one of the main challenges of public health and health policies in Europe and worldwide, especially in terms of care concepts for people with dementia. In Austria and the Czech Republic the majority of elderly institutionalized persons with dementia are cared for in nursing homes. It is however unclear, how many persons living in nursing homes in Austria and in the Czech Republic are suffering from cognitive impairment and dementia. In addition, basic information on the nutritional status, the status of mobility and the medication prescription patterns are often missing. To facilitate new effective and evidenced based care concepts, basic epidemiological data are in urgent need. Thus, DEMDATA was initiated to provide important basic data on persons living in nursing homes in Austria and the Czech Republic for future care planning. METHODS: DEMDATA is a multicentre mixed methods cross-sectional study. Stratified and randomly drawn nursing homes in Austria and the Czech Republic are surveyed. The study protocol used in both study centres assesses four different domains: a) Resident, b) Care team, c) Relative and d) Environmental Factors. Resident’s data include among others health status, cognition, dementia, mobility, nutrition, behavioural symptoms, pain intensity and quality of life. A minimum of 500 residents per country are included into the study (N = 1000 residents). The care team is asked about the use of the person-centred care and their burden. The relatives are asked about the number of visits and proxy-rate the quality of life of their family member. All staff employed in the nursing homes, all residents and relatives can voluntary take part in the study. The environmental factors include among others the organisational category of the nursing home, number of residents, number of rooms, social activities and the care concept. The project started in March 2016 and will be concluded in February 2018. DISCUSSION: DEMDATA will provide important epidemiological data on four different nursing home domains in Austria and the Czech Republic, with a focus on the prevalence of dementia in this population. Thereby supplying decision and policy makers with important foundation for future care planning.